Signatures of CD4+ T and B cells are associated with distinct stages of chronic chagasic cardiomyopathy - Vale, Isabela Natália Pascoal Campos do; Almeida, Gregório Guilherme; Rimkute, Inga; Liechti, Thomas; Araújo, Fernanda Fortes de; Santos, Luara Isabela dos; Henriques, Priscilla Miranda; Rocha, Manoel Otávio da Costa; Elói-Santos, Silvana Maria; Martins−Filho, Olindo Assis; Roederer, Mario; Sher, Alan; et al. (Frontiers in Immunology, 2024)
Chagas disease is a neglected parasitic disease caused by Trypanosoma cruzi. While most patients are asymptomatic, around 30% develop Chronic Chagasic Cardiomyopathy (CCC). Here, we employed high-dimensional flow cytometry to analyze CD4 + T and B cell compartments in patients during the chronic phase of Chagas disease, presenting the asymptomatic and mild or moderate/severe cardiac clinical forms. Effector CD27 -CD4 + T cells were expanded in both CCC groups, and only mild CCC patients showed higher frequencies of effector memory and T follicular helper (Tfh) cells than healthy donors (CTL) and asymptomatic patients. Unsupervised analysis confirmed these findings and further revealed the expansion of a specific subpopulation composed of Tfh, transitional, and central memory CD4 + T cells bearing a phenotype associated with strong activation, differentiation, and exhaustion in patients with mild but not moderate/severe CCC. In contrast, patients with mild and moderate/severe CCC had lower frequencies of CD4 + T cells expressing lower levels of activation markers, suggesting resting status, than CTL. Regarding the B cell compartment, no alterations were found in naïve CD21 -, memory cells expressing IgM or IgD, marginal zone, and plasma cells in patients with Chagas disease. However, expansion of class-switched activated and atypical memory B cells was observed in all clinical forms, and more substantially in mild CCC patients. Taken together, our results showed that T. cruzi infection triggers changes in CD4 + T and B cell compartments that are more pronounced in the mild CCC clinical form, suggesting an orchestrated cellular communication during Chagas disease. Overall, these findings reinforce the heterogeneity and complexity of the immune response in patients with chronic Chagas disease and may provide new insights into disease pathology and potential markers to guide clinical decisions.